แนวทางการฟื้นฟูประเพณีตานตอด (THE GUIDELINES TO “TAN TOD” TRADITION) - งามประภาสม, ปวีณา (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2014)
งานวิจัยเรื่อง แนวทางการฟื้นฟูประเพณีตานตอด มีวัตถุประสงค์เพื่อสำรวจประวัติศาสตร์ความเป็นมา พัฒนาการและสถานการณ์ในปัจจุบันของประเพณีตานตอด และวิเคราะห์หาแนวทางการฟื้นฟูประเพณีตานตอดอย่างเป็นระบบแบบแผนสอดคล้องกับวิถีการดำเนินชีวิตของประชาชนในชุมชนบ้านปงหอศาล หมู่ 2 ตำบลป่าตัน อำเภอแม่ทะ จังหวัดลำปาง โดยใช้วิธีการวิจัยเชิงคุณภาพผ่านการสัมภาษณ์และการสนทนากลุ่ม ผลการวิจัยพบว่า ประเพณีตานตอดเป็นประเพณีที่มีการสืบทอดมาตั้งแต่สมัยโบราณและมีการปฏิบัติสืบต่อกันมาเรื่อยๆ จนถึงปัจจุบัน แต่ในปัจจุบันนี้ประเพณีนี้ได้มีการปฏิบัติกันน้อยมาก เนื่องมาจากมีวัฒนธรรมจากโลกตะวันตกเข้ามาในหมู่บ้านอย่างแพร่หลายทำให้เกิดความต่างคนต่างอยู่ และประชาชนในชุมชนได้ลืมที่จะอนุรักษ์ขนบธรรมเนียมประเพณีดั้งเดิม แต่เมื่อไม่นานมานี้ทางผู้ใหญ่บ้านได้มีการรื้อฟื้นประเพณีนี้ขึ้นเพื่อฟื้นฟูประเพณีดั้งเดิม โดยได้มีการปรับเปลี่ยนรูปแบบวิธีการให้สอดคล้องกับสถานการณ์ในปัจจุบัน แต่พบว่ายังมีชาวบ้านบางกลุ่มที่ไม่รู้จักและยังไม่ได้ให้ความสนใจต่อประเพณีนี้เท่าที่ควร ดังนั้น เพื่อให้ประเพณีนี้ ยังคงอยู่ต่อไปจึงควรมีแนวทางในการอนุรักษ์ฟื้นฟูประเพณีตานตอด ดังนี้ 1. จัดงานประเพณีตานตอดเป็นประจำทุกปี 2. ดึงและกระตุ้นให้ชาวบ้านเข้าร่วมกิจกรรมโดยการประชาสัมพันธ์ให้ทั่วถึง 3. ถ่ายทอดประเพณีตานตอดให้แก่กลุ่มเด็กและเยาวชน โดยจัดให้ผู้สูงอายุและเยาวชนได้มาพบปะกันและถ่ายทอดประเพณีเก่าแก่ของหมู่บ้านผ่านวิธีมุขปาฐะ เพื่อสร้างจิตสำนึกในวัฒนธรรมประเพณีของชุมชน 4. ส่งเสริมให้หน่วยงานภาครัฐ โดยเฉพาะเทศบาลป่าตันได้เข้ามามีส่วนร่วมในการจัดประเพณีตานตอดและช่วยประชาสัมพันธ์ประเพณีดังกล่าว และ 5. ตั้งเป็นหมู่บ้านต้นแบบของประเพณีตานตอด 6. มีการสื่อสารประชาสัมพันธ์กิจกรรมงานประเพณีให้คนในชุมชน รวมถึงคนภายนอกได้รับทราบอย่างทั่วถึงและต่อเนื่อง คำสำคัญ: การฟื้นฟู ประเพณีท้องถิ่น ทานทอดหรือตานตอด The objectives of this Guideline to “Tan Tod” Traditional Research are to study the cultural Tan Tod’s history, evolution and present situation and to identify the systemic ways to restore the tradition in a pattern consistent with the lifestyle of the people at the Ban Pong Hor San community, village Moo 2, Patan Sub-district, Maetha District, Lampang Province. Using qualitative research through interviews and group discussions. The results show that the Traditional Tan Tod is a tradition which has been carried on since ancient times and succeeded to reserve from time to time until the present time. But today this tradition has been practiced very little because the culture from the West which moves rapidly into the village increases the relationship separation among people in the community and reduces the preservation of the cultural tradition. In the recent years, it has been restored by a village headman by modifying its basis components to make it fit to the current subsistence situation. However, there are some groups of people who do not recognize and pay attention to this traditional as well. If we want to keep this tradition to be continued, we should have some guidelines for conservation of this tradition. First, the traditional festival should be held annually. Second, the people should be encouraged to participate with the festival by covering overall public relations. Third, pass on knowledge about the life of traditional Tan Tod to the children and youth by arranging the elderly and young people’s meeting and transferred through oral traditional method to create awareness of the cultural tradition of the community. Fourth, to encourage the public sectors, especially in the Patan Local Municipality, to involve in organization and helping to promote the Tan Tod traditional culture. And fifth, from the village to be a good model of Tan Tod traditional culture for other villages. Keywords: Recover, Local Tradition, Tan Tod